KOMUNIKASI DALAM AL-QUR’AN DAN KAITANNYA DENGAN PENDIDIKAN - Asad Asad (Tazkiya: Jurnal Pendidikan Islam, 2020)
Education and learning is a process never be separated from communication activities. It can be said, learning is a communication activity itself, because teaching is conveying subject matter by educators and recipients of material by students. This activity is communication. Accordance with the understanding of the communication namely; sending and receiving messages or news between two or more people, where messages are sent by the teacher and received by students. (Anton M. Mulyono, Editor "Big Indonesian Dictionary), Jakarta Balai Pustaka, 1995 : 454. Therefore, the teacher as an educator also needs to master communication techniques so that he can communicate the subject matter to students properly and correctly. Kata kunci : Komunikasi, al-Qur’an, Pendidikan.